Analisis Pemberian Pembiayaan Pada PT. BPRS Al-Washliyah Medan - Khaidir; Sarwo Edi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to determine the procedure for granting credit, as well as the obstacles that occur in collecting non-performing loans at PT. BPRS Al Washliyah Medan. The results showed that the procedure for giving credit to PT. BPRS Al Washliyah Medan has been running well such as customers applying for credit to service customers, filling out the credit application sheet (APK) then given to the credit administration. Then it is handed over to the account officer (AO). The account officer conducts interviews and surveys on the spot. After that, make a credit analysis report (LAK) to be submitted to the credit committee, then decide whether or not the credit application is accepted. The credit administration accepts credit application applications and credit analysis reports to be kept as archives. Furthermore, the credit administration makes a credit approval (SPK) of 2 sheets accompanied by the customer's signature. Sheet 1 is for credit administration and sheet 2 is for customers. Based on the approved SPK, the credit administration makes a credit agreement (PK) of 2 sheets, sheet 1 for tellers and sheet 2 for accounting. The teller notifies the customer about the binding. Furthermore, the customer provides the original guarantee, then the teller realizes and provides credit guarantee to the customer. The original collateral is handed over to the credit administration as an archive. Based on the credit agreement, accounting conducts bookkeeping and submits the credit agreement sheet to the credit administration as an archive. The credit administration received the original guarantee and credit agreement to be used as an archive of PT. BPRS Al Washliyah Medan. Problems in collecting non-performing loans at PT. BPRS Al Washliyah Medan from the banking side minsally in conducting analysis, the manager or credit department is not careful, so that what should happen, is not predicted in advance from the customer. From the customer's own side, credit congestion can occur due to two things, namely: There is an element of intentionality. In this case, the customer deliberately does not intend to pay his obligations to PT. BPRS Al Washliyah Medan, so the credit given is bad. It can be said that there is no security element to pay. The presence of an element is accidental. This means that customers want to pay but can't afford it. Example: credit financed experiencing a disaster such as fire, flood or bankruptcy. So to pay the credit does not exist.